MEKANISME KAPITALISASI DALAM ERA JAMINAN KESEHATAN NASIONAL - Yusup, Maulana (Majalah Bisnis & IPTEK, 2021)
Implementation of the National Health Insurance (JKN) in 2014 for individual health is the development of the Health Insurance that is now available is the Community Health Insurance (Assurance), Health Insurance Childbirth (Jampersal) and the Regional Health Insurance (Jamkesda). Experience the implementation of health insurance there are now becoming the reference material at the same time learning materials in the implementation of the National Health Insurance that will begin in 2014. The implementation of JKN not be separated from the preparedness of health systems and health financing system that is now in an effort to optimize to support the implementation of the National Health Insurance. Keywords: national health insurance; capitalization